Development of ESAT-6 Based Immunosensor for the Detection of Mycobacterium tuberculosis - Omar, Rishabh Anand; Verma, Nishith; Arora, Pankaj Kumar (Frontiers in Immunology, 2021)
Early secreted antigenic target of 6 kDa (ESAT-6) has recently been identified as a biomarker for the rapid diagnosis of tuberculosis. We propose a stable and reusable immunosensor for the early diagnosis of tuberculosis based on the detection and quantification of ESAT-6 via cyclic voltammetry (CV). The immunosensor was synthesized by polymerizing aniline dispersed with the reduced graphene oxide (rGO) and Ni nanoparticles, followed by surface modification of the electroconductive polyaniline (PANI) film with anti-ESAT-6 antibody. Physicochemical characterization of the prepared materials was performed by several analytical techniques, including FE-SEM, EDX, XRD, FT-IR, Raman, TGA, TPR, and BET surface area analysis. The antibody-modified Ni-rGO-PANI electrode exhibited an approximately linear response (R2 = 0.988) towards ESAT-6 during CV measurements over the potential range of -1 to +1 V. The lower detection limit for ESAT-6 was approximately 1 ng mL-1. The novelty of this study includes development of the reusable Ni-rGO-PANI-based electrochemical immunosensor for the early diagnosis of tuberculosis. Furthermore, this study successfully demonstrates that electro-conductive PANI may be used as a polymeric substrate for Ni nanoparticles and rGO.